2021
DOI: 10.1021/acs.biomac.1c00161
|View full text |Cite
|
Sign up to set email alerts
|

Control of Structural Coloration by Natural Sunlight Irradiation on a Melanin Precursor Polymer Inspired by Skin Tanning

Abstract: Natural melanin affects the reflection and absorption of light, and it is known as an important element in producing bright structural colors in nature. In this study, we prepared core–shell particles using a melanin precursor polymer, that is, polytyrosine (PTy), as a shell layer by the oxidative polymerization of tyrosine ethyl ester (Ty) in the presence of cerium oxide (CeO2) core particles. Inspired by skin tanning, irradiating the CeO2@PTy core–shell particles with UV or natural sunlight caused melanizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 63 publications
0
11
0
Order By: Relevance
“…Both DA-coated and MDA-coated stretching modes, respectively (Figure S2). 26,27 However, these peaks were not observed from the DMDA-coated Ti/TiO 2 surfaces. The results indicated that DA and MDA coatings proceeded through intramolecular cyclization (Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both DA-coated and MDA-coated stretching modes, respectively (Figure S2). 26,27 However, these peaks were not observed from the DMDA-coated Ti/TiO 2 surfaces. The results indicated that DA and MDA coatings proceeded through intramolecular cyclization (Figure S3).…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…Both DA-coated and MDA-coated surfaces showed characteristic peaks at 1600, 1510, 1350, and 1250 cm –1 , corresponding to ν ring (CC) stretching, ν ring (CN) stretching, ν indole (CNC) stretching, and ν­(C–O)/ν­(C–N) stretching modes, respectively (Figure S2). , However, these peaks were not observed from the DMDA-coated Ti/TiO 2 surfaces. The results indicated that DA and MDA coatings proceeded through intramolecular cyclization (Figure S3).…”
Section: Resultsmentioning
confidence: 99%
“…The Y-ADDA-added films showed stronger adhesion than that of bare LSS. In general, the phenol moiety in urushiol that has hydroxyl groups affects the adherence to the substrate surface. , In addition, the photo-oxidation of Y-ADDA by UV irradiation can induce the formation of catechol and quinone structures as active species with the introduction of additional hydroxyl groups as well as the formation of dityrosine, resulting in increased LSS film adhesion to a substrate. , This is why Y-ADDA can further increase the adhesion of LSS compared to other comparative additives during UV irradiation. With an increase in additive concentration, the number of phenol and catechol groups adhering to the substrate surface correspondingly increased, resulting in stronger adhesion.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the self-assembly of these colloidal particles provides a facile approach to producing nanostructured materials with tailored properties. If sufficiently stable and nearly monodisperse particles are used, ordered three-dimensional arrangements, termed colloidal crystals, are formed. , Such structures exhibit in brilliant, iridescent colors, ,,, mimicking their natural analogue, the opal gemstone. In contrast, when polydisperse or destabilized particle dispersions are used, less intense, angle-independent colors result. , …”
Section: Introductionmentioning
confidence: 99%